The Pelotas birth cohort study, Rio Grande do Sul, Brazil, 1982-2001 - Cesar G. Victora; Fernando C. Barros; Rosângela C. Lima; Dominique P. Behague; Helen Gonçalves; Bernardo L. Horta; Denise P. Gigante; J. Patrick Vaughan
Given the growing recognition of the importance of the life course approach for the determination of chronic diseases, birth cohort studies are becoming increasingly important. This paper describes the methods used in the 1982 Pelotas (Brazil) birth cohort study, one of the largest and longest studies of this type in developing countries. All 5,914 hospital births occurring in Pelotas in 1982 (over 99% of all deliveries) were studied prospectively. The main stages of the study took place in 1983, 1984, 1986, 1995, 1997, 2000, and 2001. More than two thousand variables are available for each subject who participated in all stages of the study. Recent phases of the study included the examination of 2,250 males when presenting for the army recruitment exam in 2000, the study of a 27% sample of men and women in 2001 through household visits, and the study of over 400 children born to the cohort women. Follow-up rates in the recent stages of the cohort were 78.9% for the army examination and 69.0% for the household visits. Ethnographic and oral health studies were conducted in sub-samples. Some recent results on blood pressure, adolescent pregnancy, and asthma are presented as examples of utilization of the data. Suggestions on lessons learned for other cohort studies are proposed.